Avaliação perceptiva pela equipe de enfermagem do choro do recém-nascido prematuro: fatores de risco na gênese da rouquidão após a extubação orotraqueal - Canova, Graziela Cristina Buzutti (2013)
This study intended to assess the perception of the NICU nursing team of preterm infants crying after orotracheal intubation and risk factors related to the genesis of hoarseness. Method: cross-sectional, observational quantitative study. The study was composed of 25 premature babies and divided in four phases. The first phase was characterized by collecting clinical and diagnostic data from patients records. It was used for statistical analysis the following data: maternal age, gestational age at birth, newborn weight, sex, age, twinning, intubation attempts, total duration of intubation and occurrence of extubation. The second phase was characterized by recording newborns crying. In the third phase, it was applied a scale adapted from RASAT scale to the nursing team, to assess the vocal perception of newborns crying. In the fourth phase, the same scale was applied to speech therapists. From the evaluation of these professionals, the babies were divided in four groups: normal (no hoarseness), mild, moderate and intense hoarseness disturb. Results: 84% of the newborns presented some degree of hoarseness. The mean gestational age at birth was 28 weeks and 5 days (25 weeks and 3 days to 34 weeks and 1 day), being the highest mean gestational age at birth found in group without hoarseness. 19 were male and 6 were female. The mean weight was 1.287,2g and standard deviation of 688,95g, having the group with light hoarseness disturb the highest average. The age of newborns varied from 2 to 89 days (18,16 days of average), having the highest mean age the group with severe hoarseness disturb. The mean time of permanence intubated was 165,52 hours and standard deviation of 277,37 hours. The group with intense hoarseness disturb obtained mean time of intubation of 330 hours (the highest between all groups). Ten cases of accidental extubation occurred, 50% (five cases) in the group with mild hoarseness disturb. The auditory-perceptive assessments of nurse technicians were those who more approximated from assessment of speech therapists (p=0,029). With regard to agreement between professionals, the nursing assistant obtained best results (Kappa coefficient=0,222) Conclusion: 84% of the newborns presented some degree of hoarseness. It wasn´t possible to recognize risk factors related to the genesis of hoarseness following orotracheal intubation in preterm newborns. The variables didn´t show statistical significance. The auditory-perceptive assessments of nurse technicians were, those who more approximated from assessment of speech therapists. With regard to agreement between professionals, the nursing assistant obtained best results